Development of V-Shape Dipole Antenna for 20 MHz Astronomical Observation - Anwar, Radial; Tariqul Islam, Mohammad; Misran, Norbahiah; Fairos Asillam, Mhd (International Journal of Engineering and Technology, 2019)
The utilization of dipole antenna has includes various applications, including communication and astronomy. It has been developed in various manners, from the simple half-wavelength wire antenna to the printed micro strip antenna. This paper presents a V-shape dipole antenna for 20 MHz radio astronomical observation. The V-shape concept is adopted to provide low impedance at terminal point for 50 ohms transmission line. It is also provide a wider beamwidth compared to the conventional half-wavelength dipole antenna, make it suitable to be used in a transient radio telescope system. Simulation result shows that the designed antenna inherits a low SWR (Standing Wave Ratio), of about 1.024, relatively wide beamwidth, up to 114Â°, and a good achievable maximum gain of 7.85 dBi at zenith direction. The prototype of the designed antenna has been constructed and installed in the antenna farm for radio astronomy research at the National Space Center of Malaysia, Banting, Selangor. Some preliminary observational data are also presented in this paper.Â Â